Extraction and physiochemical characterization of baobab (Adansonia digitata L.) seed oil and its application in the production of mayonnaise stabilized by baobab protein - Nouruddeen, Zahrau Bamalli (2018)
Baobab (Adansonia digitata L.) is a wild plant, with various uses. The leaves and the pulp from the fruit and plant are staple food for many populations in Africa, most especially in the central region of the continent. The seeds are rich in oil and protein content. In addition, the seeds have been reported to have many nutritional and medicinal benefits. However, the seeds are not widely/fully utilized for their application in the food industries. Attention on the baobab plant has always been on the fruit pulp and leaves, while the seeds have always been over looked despite the high mono and polyunsaturated fatty acid and antioxidant present in the oil and high lysine content in the protein from the seed. Studying the physical and chemical, as well as the functional properties of the oil and protein extracted from the seed will be a step forward in cooperating the oil and protein into our food system. In view of the foregoing, this study presents the characterization of the oil and protein isolate and fractions (albumin, globulin, glutelin and prolamin) extracted from the seed; modification of the oil by blending with other vegetable oils to improve its application in the food industry. The effect of egg yolk substitution with protein isolate extracted from the defatted seed of baobab on the properties of mayonnaise is also investigated. The oil was extracted from baobab seed using two different methods: Soxhlet extraction (SE) and ultrasound-assisted extraction (UAE). Results showed that, despite extraction for only 2 h, UAE yielded 18.7% crude oil, representing nearly 81% of the yield obtained with SE. Quality indices such as free fatty acid content 7.92% (SE) and 6.87% (UAE), peroxide value 3.13 meq O2/kg (SE) and 3.20 meq O2/kg (UAE) and oxidative stability 6.85 h (SE) and 6.96 h (UAE), and other physicochemical properties such as fatty acid composition, triacylglycerol profile, thermal behaviour and solid fat content of both oils were comparable. Oleic, linoleic, palmitic and stearic acids were the dominant fatty acids in the baobab oil. However, the UAE oil was slightly more viscous (54.12 cP) and yellow in color (29.33 Y) than the SE oil, indicating co-extraction of compounds not extracted with SE. γ-Tocopherol was the predominant and abundant Vitamin E isomer in the oil and was found to be higher in UAE (626.01mg/g) compared to SE (536mg/g). Phenolic content 509.47 mg GAE/mg, flavonoid content 44.17 ug QE/g and IC50 of 133.43 ug/ml where predominant in UAE sample compared to SE. Baobab proteins were extracted as isolate and fractions; the isolate yield was 50.40% while the yield for the fractions were albumin 38.73%, globulin 39.63%, glutelin 18.87% and prolamin 6.00%. Extract from the defatted seeds were evaluated for their physicochemical properties (isoelectric point, bulk density, color, and amino acid profile) and functional properties (Emulsion and foaming capacity, water and oil absorption, solubility and gelation). Results show that the protein isolate was significantly higher in the emulsion (69.3%) and emulsion stability (48.5%), foaming (68.10%) and foaming stability after 60 min (23%), water and oil absorption capacity (142% and 62.51%) compared to the fractions (albumin, globulin, glutelin and prolamin). Turbidity measurement shows the following isoelectric points: baobab protein isolate (pH 3.5) and fractions; albumin (pH 4.5), globulin (pH 6), and glutelin (pH 6.5), respectively. Prolamin was not precipitated upon pH adjustment but was precipitated using cold acetone. Solubility of the protein isolate and fractions (albumin, globulin and glutelin) showed an increase in solubility as the pH increased until both samples reached their isoelectric point. Baobab protein isolate (116.23 C) shows a higher denaturation followed by prolamin fraction (106 C), with lowest in albumin fraction (74.48 C). Lysine was the dominant essential amino acid in both the protein isolate and the fractions (albumin, globulin, glutelin and prolamin). Baobab oil was blended with four different oil: palm olein (PLO), coconut (CO), soybean (SBO) and sunflower oil (SFO) using 4 different ratios (90:10, 80:20, 70:30 and 50:50%). Blending baobab oil with 30% and 50% PLO increased the levels of monosaturated and saturated fat from 38.2% and 34.3% to 39.7 and 38.4%, respectively. This was found to increase the oxidative stability of baobab oil from 6.8 h to 10.27 h. Blending baobab oil with CO oil increased lauric acid content from 0.1% to 25.4% at 50:50% ratio. Blending baobab oil with soybean and sunflower oil increase the polyunsaturated level of the baobab oil. Baobab seed oil blends with 30% sunflower oil and 20% soybean oil reduce the oxidative stability index of baobab oil from 6.8 h to 5.56 h and 4.68 h. Blends of baobab oil with PLO and CO filled the cold test, while blends with SFO and SBO passed the cold test. Emulsion stability after 30 min was significantly higher in the SFO (81%) and SBO (83.9%) in 50% blends with the least stability at 50% blend with PLO (21.8%) and CO (49%). After one week of emulsion storage blends with PLO were separated. Oils with an oxidative stability of 5-6 h are used in the production of mayonnaise. Therefore, 70% baobab oil blended with 30% soybean was the perfect oil to be used in the mayonnaise production. Protein isolate from the defatted seed of baobab was used as the egg yolk substitute in the production of mayonnaise. Blend of 30:70 % soybean and baobab oil was the oil used for the mayonnaise production. Results shows that moisture content (15.81%), protein content (8.79%), and total carbohydrate content (26.30%) of the mayonnaise produced using baobab protein isolate was comparable with the mayonnaise produced from egg yolk, while the ash (3.12%) and total lipid content (44.8%) were significantly lower than the mayonnaise produced from egg yolk. Mayonnaise produced from baobab protein isolate had a higher b* (26.75) color compared to mayonnaise produced from egg yolk (20.81). Mayonnaise produced from egg yolk were lighter compared to the one produced from baobab protein isolate. Rheological properties (firmness, stickiness and adhesion and viscosity), acid and peroxide value were studied. The results show a significant difference at P<0.05 in the rheological properties between the fresh and stored sample after 4 months, while peroxide and acid value showed no significant difference at P<0.05. A 9-point hedonic scale sensory analysis was carried out with 30 panelists. Results of sensory analysis conducted on the mayonnaise produced from egg yolk and protein isolate were generally accepted with good scores, for creaminess (7.07 and 6.3), pastiness (8.3 and 7.4), stability (6.20 and 5.98) and aroma (7.6 and 5.7). The overall acceptability of the mayonnaise from egg yolk (7.27) were not significantly different at P<0.05 with protein isolate (6.71), but value wise the egg yolk mayonnaise where more acceptable.